(untitled) (The Review of Diabetic Studies, 2024)
Integrated health systems are powered by the joint proficiency, compassion, along with dedication of a wide range of medical practitioners, all working together to ensure that care goes beyond effective as well as truly patient-centered. In Saudi Arabia, these professionals manage a medical sector that is constantly growing and changing. The system is noted for expanding service coverage, rising population health needs, and the increasing complexity of medical care. This article takes a closer look at the important contributions of medical practitioners within Saudi Arabia’s integrated health systems, adopting a multidisciplinary lens to better understand how different roles come together to create a whole greater than the sum of its parts. We explore the makeup of the workforce, the spirit of cross-professional teamwork, how services are connected throughout different levels of care, and what all of this means for public health and wellness. By exploring the structures, day-to-day teamwork, and continuing difficulties these professionals face, this review shines a light on their central role in building and sustaining integrated care models and in driving the overall performance and resilience of the nation’s health system.